Application of IMC-PID Controller with integer-order filter and fractional-order filter for steam distillation essential oil extraction process / Siti Nur Hasinah Johari, Ramli Adnan and Mazidah Tajjudin - Johari, Siti Nur Hasinah; Adnan, Ramli; Tajjudin, Mazidah (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Essential oils are one of the main compounds in the pharmaceutical, fragrance and food industries. Essential oils are volatile and sensitive to heat. They can be extracted using various methods and including steam distillation which is regarded in this research. Consequently, the temperature during the extraction process is an important factor that influences the quality of essential oils. For decades the famous PID controller dominated the industrial control loop. Poor PID control tuning may result in poor control performance and even poor quality products. This study proposes an Internal Model Control (IMC) tuning method for a PID controller to control steam temperature during the extraction process. IMC suggested a model based tuning rules so that the closed-loop will be less sensitive to disturbance. Two types of IMCPID controller approaches were considered in this paper which are IMC-PID controller with integer-order filter (IOF) and IMC-PID controller with fractional-order filter (FOF). There is a single tuning parameter in IO filter, while the FO filter has two parameters to be tuned in order to achieve satisfactory response of the system. The simulation is done in Simulink using MATLAB R2018a and comparison studies are made for transient response (Tr, Ts, %Mp) for both controllers. The result has shown that the IMC-PID FOF controller gives a better response than IMC-PID IOF controller by having less overshoot (2.59%) and has fastest rise time and settling time by 264.7s and 447.4s respectively.